L’Ordre caché: La notion d’ordre chez saint Augustin. By Anne-Isabelle Bouton-Touboulic. Pp. 702. (Collection des Études Augustiniennes Série Antiquité, 174.) Paris: Institut d’Études Augustiniennes, 2004. isbn 2 85121 197 8. Paper €69 - Bonner, Gerald (The journal of theological studies, 2006)
The French can claim, not unreasonably, to be the nation which has most honoured Augustine of Hippo by the study of his writings. Behind modern scholars like Eugène Portalié, H.-I. Marrou, and Pierre Courcelle is a tradition which looks back to the monks of St-Germain-des-Prés, whose heroic labours were contrasted by Gibbon with the sloth of the ‘monks’ of his own Magdalen College, Oxford. Anne-Isabelle Bouton-Touboulic stands in this tradition, with great learning and prodigious application. Although she presumably uses a computer, like other scholars today, she is able to sort out and organize the materials which this medium is able to provide in an abundance which is apt to become unmanageable.